Pemodelan Status Usaha (Pengusaha dan Pekerja/Karyawan) Menggunakan Regresi Logistik Multilevel - eko yulian (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2017)
The level of a country's economy is directly proportional to the number of entrepreneurs in the country. According to the World Bank standard number of entrepreneurs, the ideal of a country is at least 4% of the total population. Based on data from the Indonesian Young Entrepreneurs Association (HIPMI), the number of entrepreneurs in Indonesia is only about 1.5%. Of course not easy to achieve the ideal number of bank standards-based world that is 4%. This study aims to determine what factors are driving someone in determining a career as an entrepreneur or not (worker/employee). The data used is the Adult Population Survey (APS) in 2013 conducted by the Global Entrepreneurship Monitor (GEM). the survey conducted in 16 provinces, 51 districts/cities, and 176 subdistricts. Data generated hierarchical modeling that will be performed using multilevel logistic regression. The variables studied were the state variable effort (Y), variable knowent (X1), variable opport (X2), variable suskill (X3), variable fearfail (X4), the variable gender (X5) at level 1 and the variable sub-district at level 2. the analysis showed that the logistic regression model 2-level produce a better model than the ordinary logistic regression model. Based on modeling results we concluded that all predictor variables (knowent, opport, suskill, fearfail, gender, etc.) affect the status of one's business.